Evaluation of Frontline Demonstrations on the Yield and Economic analysis of Summer Moong in Amritsar district of punjab (Indian Journal of Extension Education, 2014)
The frontline demonstrations are being used by extension experts for speedy dissemination of improved technologies and testing under location specific situations. Punjab state is divided into six Agro-climatic regions and Amritsar district falls under Central Plain Region. Nine farmers were selected randomly for popularizing summer moong in the district. With the help of front line demonstration, it was demonstrated that the improved varieties of summer moong can be added in paddy wheat rotation and additional 10.48 qt/ha pulses can be obtained with existing resources. As a result of addition of summer moong in the cropping system income of the farmers improved to the tune of ` 34,257.74 per hectare with the B:C ratio 1.82 in addition to the known benefits of pulses to the soil resources.